1988
DOI: 10.1002/ijc.2910420517
|View full text |Cite
|
Sign up to set email alerts
|

Plasma membrane lipid composition of vinblastine sensitive and resistant human leukaemic lymphoblasts

Abstract: Plasma membranes purified 32- to 45-fold were isolated from leukaemic T-lymphoblasts, both sensitive and resistant to the Vinca alkaloid vinblastine. On development of drug resistance there was a very significant elevation of ether lipid content. 1-0-alkyl phospholipid increased by 200% with a smaller 30% increase in 1-0-alkenyl phospholipid. Cholesterol and phospholipid levels were also found to increase by 50% and 30% respectively, while the lipid to protein ratio increased by 60%. More modest changes were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
54
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 31 publications
4
54
0
Order By: Relevance
“…For instance, in vinblastine-resistant leukemic lymphoblasts, cholesterol and phospholipids levels were found to increase by 50% and 30% respectively, while the lipid to protein ratio increased by 60%. 36 The analysis by freeze-fracture electron microscopy, besides confirming the remarkable increase of vesicular structures inside VOA-treated cells, furnished further ultrastructural details on the autophagosome formation and on their structural differences between sensitive and resistant cells. The freeze-fracture images have to be interpreted on the basis of the various models proposed for the autophagosome formation.…”
Section: Methodsmentioning
confidence: 70%
“…For instance, in vinblastine-resistant leukemic lymphoblasts, cholesterol and phospholipids levels were found to increase by 50% and 30% respectively, while the lipid to protein ratio increased by 60%. 36 The analysis by freeze-fracture electron microscopy, besides confirming the remarkable increase of vesicular structures inside VOA-treated cells, furnished further ultrastructural details on the autophagosome formation and on their structural differences between sensitive and resistant cells. The freeze-fracture images have to be interpreted on the basis of the various models proposed for the autophagosome formation.…”
Section: Methodsmentioning
confidence: 70%
“…15 Of note, cholesterol level was found to increase by as much as 50% in some multidrug resistant cells in comparison with their parental cells. 42,43 Present study showed that Pgp-expressing leukemia cell lines K-562/ADR, NOMO-1/ADR and NB4/RA/MDR were more sensitive to lovastatin than their parental cell lines in terms of inhibition of proliferation and induction of apoptosis. However, despite the high expression of MDR-1 mRNA and Pgp on membrane, the MDR-1 genetransduced variant of NB4, NB4/MDR, was not more sensitive to lovastatin, showing equal sensitivity to lovastatin as their parental cells.…”
Section: Figurementioning
confidence: 68%
“…Reports show that P-gp ATPase activity is dependent on the lipid environment (5), and lipids interact with P-gp substrates (6). Differences in glycerolipid and sphingomyelin compositions of multidrug-resistant and drug-sensitive cells have been reported (7)(8)(9)(10)(11), and ganglioside composition of multidrug-resistant and drug-sensitive cells has been examined. Whereas diversity in ganglioside composition was revealed, no definitive correlation with drug resistance was demonstrated (7,12).…”
mentioning
confidence: 99%